A Systematic Literature Review on the Relationship Between Quality of Work and Intentions to Retire Among Individuals Aged 50 and Older - Kairys, Antanas; Sadauskaitė, Raimonda; Zamalijeva, Olga; Guðmundsson, Halldór S.; Reine, Ieva; Sakkeus, Luule; Tomsone, Signe (Socialinė teorija, empirija, politika ir praktika, 2024)
Europe, notably in countries like Lithuania, is facing substantial demographic shifts due to aging, impacting various systems, including the labor market. In this context understanding retirement intentions is crucial. Quality of work is a key determinant of retirement intentions, yet other factors such as financial situation, health, or family pressures also play a role, and a comprehensive understanding of their interactions remains a research gap. Therefore, the aim of this study was to conduct a systematic literature review of research on the relationship between retirement intentions and quality of work, with a specific focus on potential control factors, moderators and mediators of this relationship. This systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta Analyses (PRISMA). Articles were electronically retrieved from Scopus, Web of Science, ScienceDirect, and EBSCO databases. Studies selected were full-text, peer-reviewed articles in English from 2003 to 2023, which used quantitative methodologies and focused on the relationship between retirement intentions and quality of work for workers aged 50+. The quality of the selected publications was assessed using the Appraisal Tool for Cross-Sectional Studies – AXIS tool. Of the initial 776 sources, after removing duplicates and irrelevant articles, 91 were fully screened, and 17 met the criteria for inclusion in the systematic review. This systematic literature review provided further insights into the relationship between retirement intentions and quality of work, highlighting the roles of moderators, mediators, and control factors in this relationship.